2019
DOI: 10.1101/809129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic determinants of multi-drug resistance inAcinetobacter baumanniiat an academic hospital in Pretoria, South Africa

Abstract: 24Antimicrobial resistance is now globally recognised as the greatest threat to human 25 health. Acinetobacter baumanniis' (A. baumannii) clinical significance has been driven by its 26 ability to obtain and transmit antimicrobial resistance factors. In South Africa, A. baumannii 27 is a leading cause of healthcare associated infections (HAI). In this study, we investigated the 28 genetic determinants of multi-drug resistant A. baumannii (MDRAB) at a teaching hospital in 29 Pretoria, South Africa. 30One hundre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Piperacillin-tazobactam is known to be a key antibiotic against A. baumannii [51]. Contrary to our results (resistance rate of 31.3%), several studies have reported a high prevalence of resistance to piperacillin-tazobactam, ranging from 62 to 100% in Benin, Tanzania, Ghana, Morocco, and South Africa [52,53].…”
Section: Discussioncontrasting
confidence: 99%
“…Piperacillin-tazobactam is known to be a key antibiotic against A. baumannii [51]. Contrary to our results (resistance rate of 31.3%), several studies have reported a high prevalence of resistance to piperacillin-tazobactam, ranging from 62 to 100% in Benin, Tanzania, Ghana, Morocco, and South Africa [52,53].…”
Section: Discussioncontrasting
confidence: 99%
“…Kim et al [47] stated the high A. baumannii prevalence (27.80%) amongst the raw milk samples which is supported by the high antibiotic resistance of isolates against ceftriaxone (4.4%), tetracycline (30.8%), gentamicin (2.9%), and cefotaxime (12.5%). Similarly, in surveys conducted on Iran [48], Brazil [49], Jordan [50], United States [51], Korea [52], and Africa [53], high A. baumannii resistance rates against tetracycline, ampicillin, gentamicin, trimethoprim, ciprofloxacin, and erythromycin were reported. Askari et al [21] stated that the A. baumannii strains isolated from raw meat of animal species harbored the highest resistance rate against tetracycline (82.35%), gentamycin (74.50%), streptomycin (54.90%), cotrimoxazole (70.58%), and trimethoprim (62.74%).…”
Section: Discussionmentioning
confidence: 88%
“…In keeping with this, this pathogen's role in seafood samples is potentially unknown, and further research is required to understand this fact. High prevalence of resistance of A. baumannii strains toward commonly-used antimicrobials, particularly tetracycline, gentamicin, ciprofloxacin, trimethoprim, streptomycin, and erythromycin was reported from Brazil [41], Iran [42], United States [43], Jordan [44], Africa [45], and Korea [46].As antibiotic-resistant A. baumannii was detected in large number of seafood samples. Proper monitoring of the seafood microbial quality should perform at the site of fishing and also after their transport.…”
Section: Discussionmentioning
confidence: 99%